Advances in Acute Ischemic Stroke Therapy. Issue 8 (15th April 2022) - Xiong, Yunyun; Wakhloo, Ajay K.; Fisher, Marc
Abstract : The treatment of acute ischemic stroke continues to advance. The mainstay of treatment remains intravenous thrombolysis with alteplase. Recent studies demonstrated that later treatment with alteplase is beneficial in patients selected with advanced imaging techniques. Tenecteplase has been evaluated as an alternative thrombolytic drug and evidence suggests that it is as least as effective as alteplase and may lyse large vessel clots more effectively. Endovascular therapy with mechanical thrombectomy has now been shown to be beneficial up to 24 hours after stroke onset in carefully selected patients with proximal, large vessel occlusions. Ongoing studies are evaluating the effectiveness of thrombectomy in patients with more distal vessel occlusions and patients with proximal large vessel occlusions with larger ischemic core volumes and also in patients with milder neurological deficits. Cytoprotection is another potential acute stroke therapy that has not demonstrated efficacy in prior clinical trials. It should be reconsidered as an adjunct to reperfusion and a variety of new clinical trials can be envisioned to evaluate the potential benefits of cytoprotection in patients before and after reperfusion.